Математика | 216 қаралды
216 қаралды
Екімүшенің толық квадратын айыру f(x)=3х"-х-5 ( "- деген ол квадрат)
                                                               f(x)=4x"-x-2
f(x)=2x"-10х+1
f(x)=2/3*х"-3х-3*3/1

1 жауап

3x²-x-5=(V3)²*x²-2*1*V3/2 *x*1/2V3 +(1/2V3)²-(1/2V3)²-5=0  //V - түбір асты белгісі

f(x)=3х"-х-5=[(V3)*x-1/2*(V3)]²-61/12

 f(x)=4x"-x-2=(2x)²-2*2x*1/4+(1/4)²-(1/4)²-2

 f(x)=4x"-x-2=(2x-1/4)²-2,0625

f(x)=2x"-10х+1=((V2)*x)²-2*(V2)*x*5/V2+(5/V2)²-(5/V2)²+1

f(x)=2x"-10х+1=[(V2)*x-5/V2]²-11,5

f(x)=2/3*х"-3х-3*3/1=[(V{2/3})*x]²-2*V{2/3}*x*3/2*V{2/3}+(3/[2*V{2/3}])²-(3/[2*V{2/3}])²-3=(V{2/3}*x-3/[2*V{2/3}])²-3-9/(4*2/3)=(V{2/3}*x-3/[2*V{2/3}])²-3-9/14/3=(V{2/3}*x-3/[2*V{2/3}])²-3-27/14=(V{2/3}*x-3/[2*V{2/3}])²-69/14=(V{2/3}*x-3/[2*V{2/3}])²-4,92857143

118,323 сұрақ
305,126 жауап
153,293 пікір
67,473 қолданушы